Effect of Graded Level of Alphamune G on Performance, Blood Chemistry and Histology of Cockerel Chicks - Bolu, S.A.; Ojo, V.; Oluyemi, O.; Babawale, O.I.; Awodele, O.A. (International Journal of Poultry Science, 2009)
A study was conducted to determine the response of day-old cockerel chicks to graded levels of Alphamune G (0.00, 0.04, 0.05 and 0.06%). The experiment which was conducted for 8 weeks employed a completely randomized design. Feed intake and nutrient retention were not significantly influenced (p>0.05) by dietary inclusion levels of Alphamune G. However, weight gain and feed to gain ratio were significantly improved (p<0.05) for cockerel chicks fed 0.06% inclusion level when compared with the control. The values were 7.78 and 4.58 g/bird/week, respectively. Haematology and serum indices did not show any significant effect as a result of the graded levels of dietary Alphamune G. Histological characteristics revealed slight morphological changes in specific organs of birds fed Alphamune G supplemented diet vis-a viz the control diet. Inclusion of Alphamune G at 0.06% in the diets of cockerel chicks gave the best performance.